Optimizing operational efficiency in automotive maintenance SMES through PDCA integration and systematic layout planning - Garcia Calderon Mendoza Del Solar, Daniel (2024)
The small and medium-sized enterprises (SMEs) in the automotive maintenance service sector are essential for the global economy and particularly for Peru. These SMEs face significant challenges related to inefficiency in their maintenance processes, often resulting in high levels of unproductive time and inadequate workflow management. This study arises from the need to optimize the operational efficiency of these businesses through the implementation of planning and continuous improvement methodologies. The main contribution of this research is the development and implementation of a service model based on the PDCA (Plan-Do-Check-Act) cycle, complemented by Systematic Layout Planning (SLP) and Value Stream Mapping (VSM) techniques. This structured model allowed the identification and elimination of non-value-added activities, optimization of workshop layout, and improvement of workflow efficiency. The most outstanding results of the model implementation include a 30% reduction in distances traveled within the workshop, a 15% decrease in service cycle times, a 10% increase in customer satisfaction, and a 5% improvement in overall operational efficiency. These indicators demonstrate that the proposed model not only addressed inefficiency issues but also established a solid foundation for future optimizations, aligning with Lean Service principles and ensuring the sustainability of long-term improvements.